The Issue of Dual-Morphemes in Arabic: A Morpho-Syntax Study - Mochammad Indra Yumanto; Mohammad Nurunnasry; Abdoul Jabalibizmungu (Journal of Arabic Language Studies and Teaching, 2021)
This research aims to find out the different arguments and opinions about the Morpheme “Tatsniyah”. The research combined morphological and structural studies in their analysis of the placement of words in the sentence, and the method used by the researcher in this issue is the descriptive approach, where the researcher described the problematic facts of the Morpheme “Tatsniyah” in the Arabic language. The result of this study are The first, opinions of nahwu scholars on the morpheme “Alif” in “Tatsniyah” : (a) the morpheme “Alif” is the letter “I’rob”. (b) the morpheme “Alif” is “I’rob”. (c) the morpheme “Alif” is the proposition “I’rob”. (d) the morpheme “Alif” is “Mabni”. (e) the morpheme "Alif" is not to be confused with "isim". (f) determining the morpheme "Alif" in the situation of "rofa', nashab, and jer". The second, function of the "nun" morpheme in “Tatsniyah”: (a) substitute for “harakat” and “tanwin”. (b) substitute for “harakat”. (c) substitute for “tanwin”. (d) address for the absence of “idhofah”. The third, determinations of the “Tatsniyah” morpheme are seen from several aspects: (a) from the aspect of its use, (b) from the aspect of word classification, (c) from the aspect of its affixation.